Identifying and Characterizing Types of Balance Recovery Strategies Among Females and Males to Prevent Injuries in Free-Standing Public Transport Passengers - Xu, Jia-Cheng; Silvano, Ary P.; Keller, Arne; Krašna, Simon; Thomson, Robert; Klug, Corina; Linder, Astrid (Frontiers in Bioengineering and Biotechnology, 2021)
Free-standing passengers on public transport are subjected to perturbations during non-collision incidents caused by driver maneuvers, increasing the risk of injury. In the literature, the step strategy is described as a recovery strategy during severe perturbations. However, stepping strategies increase body displacement, ultimately subjecting passengers to higher risk of impacts and falls on public transport.. This study investigates the influence of different recovery strategies on the outcome of balance recovery of free-standing public transport passengers, challenged in postural balance by the non-uniform vehicle dynamics. From high-speed video recordings, a qualitative investigation of the balance responses of volunteer participants in a laboratory experiment was provided. On a linearly moving platform, 24 healthy volunteers (11 females and 13 males) were subjected to perturbation profiles of different magnitude, shape and direction, mimicking the typical acceleration and deceleration behavior of a bus. A methodology categorizing the balancing reaction to an initial strategy and a recovery strategy, was used to qualitatively identify, characterize and, evaluate the different balance strategies. The effectiveness of different strategies was assessed with a grading criterion. Statistical analysis based on these ordinal data was provided.